2012
DOI: 10.1073/pnas.1203013109
|View full text |Cite
|
Sign up to set email alerts
|

Determination of solution structures of proteins up to 40 kDa using CS-Rosetta with sparse NMR data from deuterated samples

Abstract: We have developed an approach for determining NMR structures of proteins over 20 kDa that utilizes sparse distance restraints obtained using transverse relaxation optimized spectroscopy experiments on perdeuterated samples to guide RASREC Rosetta NMR structure calculations. The method was tested on 11 proteins ranging from 15 to 40 kDa, seven of which were previously unsolved. The RASREC Rosetta models were in good agreement with models obtained using traditional NMR methods with larger restraint sets. In five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
234
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(238 citation statements)
references
References 44 publications
2
234
0
2
Order By: Relevance
“…Chemical shifts hold valuable structural information that is being used more and more in the determination and refinement of protein structures and dynamics (Mulder and Filatov, 2010;Raman et al, 2010;Lange et al, 2012;Bratholm et al, 2015;Robustelli et al, 2010) with the aid of empirical shift predictors such as CamShift (Kohlhoff et al, 2009), Sparta+ (Shen and Bax, 2010), ShiftX2 (Han et al, 2011), PPM One (Li and Brüschweiler, 2015) and shAIC (Nielsen et al, 2012). These methods are typically based on approximate physical models with adjustable parameters that are optimized by minimizing the discrepancy between experimental and predicted chemical shifts computed using protein structures derived from x-ray crystallography.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical shifts hold valuable structural information that is being used more and more in the determination and refinement of protein structures and dynamics (Mulder and Filatov, 2010;Raman et al, 2010;Lange et al, 2012;Bratholm et al, 2015;Robustelli et al, 2010) with the aid of empirical shift predictors such as CamShift (Kohlhoff et al, 2009), Sparta+ (Shen and Bax, 2010), ShiftX2 (Han et al, 2011), PPM One (Li and Brüschweiler, 2015) and shAIC (Nielsen et al, 2012). These methods are typically based on approximate physical models with adjustable parameters that are optimized by minimizing the discrepancy between experimental and predicted chemical shifts computed using protein structures derived from x-ray crystallography.…”
Section: Introductionmentioning
confidence: 99%
“…This information has been used to characterize protein secondary structures (17,18) and to determine the allowed ranges of dihedral angles (19). More recently it has been demonstrated that by encoding the chemical shift information into molecular fragments it is possible to accurately determine the structures of smallto medium-sized globular proteins (14)(15)(16)(20)(21)(22)(23).…”
mentioning
confidence: 99%
“…Instead, we used resolution-adapted structural recombination (RASREC) Rosetta, a novel structure determination strategy combining NMR experimental data with database-derived conformational sampling (16)(17)(18)(19), allowing the structures of poorly behaved, larger proteins to be solved (16,17). To increase sensitivity, NMR data were collected on deuterated samples (20).…”
Section: Significancementioning
confidence: 99%